VALUE OF CLINICAL PULMONARY INFECTION SCORE IN CRITICALLY ILL PATIENTS: BETWEEN THE USE OF CHLORHEXIDINE AND PIPER BETLE LINN MOUTHWASH - Irfany Nurul Hamid; Rr Sri Endang Pujiastuti; Dwi Ari Widigdo; Djenta Saha (Belitung Raya Foundation, Indonesia, 2018)
Background: One of the complications of ventilator use in patients in Intensive Care Unit (ICU) is Ventilator-Associated Pneumonia (VAP). Oral hygiene is one of the methods to prevent VAP. Objective: The objective of this study was to compare the value of clinical infection score (CPIS) in critically ill patients after given oral hygiene using chlorhexidine and Piper betle Linn mouthwash. Methods: This was an observational study with cross-sectional study design, which consisted of two intervention groups. Thirty respondents were selected using total sampling, with 15 respondents randomly assigned in each group. Independent t-test was used for data analysis. Results: Findings showed that the mean of CPIS in the Piper betle Linn group was 3.80 and the mean of CPIS in the chlorhexidine group was 4.07. Conclusion: CPIS in the treatment group using Piper betle Linn mouthwash was lower than the mean of CPIS in the treatment group using chlorhexidine.